The Analysis of Language Politeness Used by Famous Child (Range 5-13 Years) - Alfiyatu Nuuriyyah Aa Minatul Imaamah; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
Politeness has an important role in communication. It is used not only by adults, but also by young people. This study aims to identify and describe politeness use among famous children in the video of